(untitled) (Veterinary Science, 2017)
In the ground of public areas, it can be possible to find different infective forms of canine nematode that affect the human and animal health. The children are especially susceptible to be infected with the parasitic disease in those areas because its behaviour, playing on the ground, in close contact with animals faeces. The objective of the present work was to determine the occurrence of zoonotic nematodes in dog faeces found in public areas surrounding of the Brown Health Centre, in the city of General Pico, La Pampa from 2013 to 2015. Dog faeces from the animals and from the ground were collected in the mentioned public areas. The results showed that 50 to 58% of dog faeces, and 21,1% to 52,2% of ground faeces were positive, depending on the year, with zoonotic nematode, being Ancylostoma spp. the predominant parasite. It would be important implement preventive activities in the Health Centres areas, under the concept one world one health